Doing cross cultural research in adult education: Methodological and epistemological considerations. - Barbara Sparks (Adult Education Research Conference, 1997)
While doing cross cultural research is not new, the growing acknowledgement of the perils of crossing cultures unconsciously is gaining support and calling for change. This paper examines some methodological and epistemological considerations of doing cross cultural qualitative research in adult education. Reliance on partial knowledge and middle class cultural and political bias point to the need within the field for critical reflection on how and why empirical realities are studied in the ways that they are and at the same time require rethinking and revision of traditional research methods while designing new methods of inquiry.